Impact of active dose management on radiation exposure and image quality in computed tomography: An observational study in 1315 patients. Issue 125 (April 2020) - Poehler, Gesa H.; Alikhani, Babak; Klimes, Filip; Hauck, Erik F.; Ringe, Kristina I.; Sonnow, Lena; Wacker, Frank; Raatschen, Hans-Jürgen
Graphical abstract: Highlights: Active dose management helps to reduce overall CT radiation exposure. Retrospective single-center study showed CT dose tracking and optimization. Dose surveillance stabilizes diagnostic image quality despite CT dose reduction. Abstract: Purpose: To determine the clinical impact of CT dose management team on radiation exposure and image quality. Methods: 2026 clinical routine CT examinations of 1315 patients were evaluated retrospectively. A CT dose management team was established as an integral part of the radiological department. It identified 5 CT protocols (A–E), where national reference values were exceeded the most. Those reference values included specifically the mean volumetric CT dose index (CTDIvol ) and the mean dose-length product (DLP). Baseline data (period 1) and follow up data (period 2) were obtained after reduction of tube voltage and increase of pitch or noise index. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were calculated to compare image quality. Two-sided t-tests were performed. Results: Mean CTDIvol and mean DLP of the chest protocol (A) decreased after reduction of tube voltage ( P < 0.01). In the chest/abdomen/pelvis protocol (B), the increase of noise index resulted in a significant mean CTDIvol decrease ( P < 0.02) without statistical significance of mean DLP ( P < 0.12). In the abdomen/pelvis protocol (C), mean CTDIvol ( P = 0.01) and mean DLP ( P < 0.01) were significantly lower after noise index increase. In the staging of hepatocellular carcinoma (D), mean CTDIvol and mean DLP were significantly lower after increase of pitch and noise index ( P < 0.01). The lung protocol (E) yielded no significant changes after modulation ( P > 0.05). SNR (protocol A) was significantly higher in period 2 ( P < 0.04). Protocol D showed significantly lower selected SNR and CNR ( P < 0.02). Conclusions: Establishing an operating dose management team as a standard for good clinical practice helps to considerably reduce CT radiation dose while preserving image quality.